2022
DOI: 10.1093/europace/euac244
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune diseases and new-onset atrial fibrillation: a UK Biobank study

Abstract: Aims The underlying mechanisms of atrial fibrillation (AF) are largely unknown. Inflammation may underlie atrial remodelling. Autoimmune diseases, related to increased systemic inflammation, may therefore be associated with new-onset AF. Methods and results Participants from the population-based UK Biobank were screened for rheumatic fever, gastrointestinal autoimmune diseases, autoimmune diseases targeting the musculoskeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Furthermore, some of the largest differences in protein-disease associations between sexes were observed for aortic stenosis. Prior histological work in aortic stenosis patients suggests distinct tissue composition differences between men and women, with women showing less valvular calcification but more fibrosis than men 40 . Building upon these findings, we identified several sex-specific senescence-associated biomarkers (e.g., IGFBP7 and TNF) associated with incident aortic stenosis in female, but not male, participants.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some of the largest differences in protein-disease associations between sexes were observed for aortic stenosis. Prior histological work in aortic stenosis patients suggests distinct tissue composition differences between men and women, with women showing less valvular calcification but more fibrosis than men 40 . Building upon these findings, we identified several sex-specific senescence-associated biomarkers (e.g., IGFBP7 and TNF) associated with incident aortic stenosis in female, but not male, participants.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Tilly et al examined the relationship between autoimmune diseases and new-onset atrial fibrillation in a large UK population [28]. Regarding IBD, it was shown that the incidence of atrial fibrillation was higher in women with Crohn's disease while in ulcerative colitis the incidence of atrial fibrillation was higher only in men [28]. It was hypothesized that the estrogen receptors may play an important role in this setting explaining why men suffered more from colitis, in contrast to women who suffered more from ileitis [28].…”
Section: Inflammatory Bowel Disease and Atrial Fibrillationmentioning
confidence: 99%
“…Moreover, they had a greater risk of requiring mechanical ventilation, developing cardiac arrest, and ICU admission [25]. Interestingly, Tilly et al examined the relationship between autoimmune diseases and new-onset atrial fibrillation in a large UK population [28]. Regarding IBD, it was shown that the incidence of atrial fibrillation was higher in women with Crohn's disease while in ulcerative colitis the incidence of atrial fibrillation was higher only in men [28].…”
Section: Inflammatory Bowel Disease and Atrial Fibrillationmentioning
confidence: 99%
“…The last decade has seen the emergence of autoimmunity as a potential contributing mechanism of cardiac arrhythmias, leading to the concept of “autoimmune cardiac channelopathies.” 5 Meanwhile, a recent cohort study based on the UK Biobank has shown that autoimmune diseases such as rheumatic fever, Crohn’s disease, ulcerative colitis, rheumatoid arthritis, polyarteritis nodosa, systemic lupus erythematosus, and systemic sclerosis were associated with a larger AF risk. 6…”
Section: Atrial Fibrillation and Autoimmunitymentioning
confidence: 99%
“…5 Meanwhile, a recent cohort study based on the UK Biobank has shown that autoimmune diseases such as rheumatic fever, Crohn's disease, ulcerative colitis, rheumatoid arthritis, polyarteritis nodosa, systemic lupus erythematosus, and systemic sclerosis were associated with a larger AF risk. 6 However, association is not causation. Inflammation by itself may promote or trigger cardiac arrhythmias, especially if an arrhythmogenic substrate preexists.…”
Section: Article See P 487mentioning
confidence: 99%